2012
DOI: 10.1111/j.1365-2265.2012.04462.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of exon 8 G533C mutation in apparently sporadic medullary thyroid carcinoma in Greece

Abstract: In our study, we found that 7·75% patients with apparently sporadic MTC do carry G533C mutation involving exon 8 of ret. We feel that there is now a need to include exon 8 mutation screening in all patients diagnosed as sporadic MTC, in Greece.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 24 publications
2
26
0
Order By: Relevance
“…This finding underlines the importance of routine calcitonin screening in detecting medullary carcinoma among patients presenting with nodular goiter, which has been extensively discussed in the literature (2,16,36). Furthermore, we have recently shown that routine calcitonin measurement may even lead to identification of unsuspected familial cases (37). Our results further support the fact that the routine calcitonin measurement helps in detecting MTCs earlier and this may lead to a better surgical treatment and final outcome as has already been discussed (16).…”
Section: Discussionsupporting
confidence: 84%
“…This finding underlines the importance of routine calcitonin screening in detecting medullary carcinoma among patients presenting with nodular goiter, which has been extensively discussed in the literature (2,16,36). Furthermore, we have recently shown that routine calcitonin measurement may even lead to identification of unsuspected familial cases (37). Our results further support the fact that the routine calcitonin measurement helps in detecting MTCs earlier and this may lead to a better surgical treatment and final outcome as has already been discussed (16).…”
Section: Discussionsupporting
confidence: 84%
“…This mutation appears to be specific to the Mediterranean region (7,12) and has rarely been found in other series. Interestingly, the first …”
Section: Variability Of Mutations Spectrum In Different Ethnic Groupsmentioning
confidence: 65%
“…Mutations in exon 10 at codons 609, 611, 618, and 620 and in exon 11 at codon 634 (5) are the commonest among the familial cases accounting for 88-98% of the cases. Less frequently, mutations have been reported in the non-cysteine RET region such as at codon 804 in exon 14, codon 883 in exon 15, and codon 533 in exon 8 (6,7). Mutations at codon 918 in exon 16 are found in 95% of MEN2B patients and appear to be specific for this syndrome (5).…”
Section: Introductionmentioning
confidence: 99%
“…Before more data are forthcoming from other countries, exon 8 may need to be scanned in addition -not just in Greek patients presenting with apparently sporadic MTC, 7.8% (ten of 129) of whom may carry mutations in codon 533 (23).…”
Section: Implications For Ret Screening Programs In the New Milleniummentioning
confidence: 99%